The Clinical Efficacy of Autologous Platelet-Rich Plasma Interventional Circulatory Perfusion Combined with Radiofrequency Ablation and Thermocoagulation in the Treatment of Discogenic Low Back Pain - Zhong-Liu Cao; Hu Xu; Jia-Qiang Wu; Jiang-Hua Dai; Si-Jian Lin; Ling-Feng Zou; Ling Yu; Hui-Chun Yang (International Journal of Clinical Practice)
Objective. In this study, we aimed to explore the efficacy of the autologous platelet-rich plasma (PRP) interventional circulatory perfusion combined with radiofrequency ablation and thermocoagulation (RFAT) in the treatment of discogenic low back pain (DLBP). Methods. From January 2020 to November 2022, 158 patients of the Second Affiliated Hospital of Nanchang University were selected as the study subjects, and 24 patients met the exclusion criteria. The 134 patients who met the inclusion criteria were divided into 65 patients in the control group (3 patients lost to follow-up) and 69 patients in the observation group (5 patients lost to follow-up), so 126 patients were actually completed the study, including 62 patients in the control group and 64 patients in the observation group. The control group responsible disc received RFAT, and an interventional circulatory perfusion was performed; the observation group received RFAT, and an interventional circulatory perfusion was performed, and then autologous PRP 2 ml was injected. Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) were performed before and 4 and 8 weeks after treatment, and the efficacy was evaluated at 4 and 8 weeks after treatment. The changes of lumbar disc MRI before and after treatment were observed. Results. The differences in the Visual Analog Scale (VAS) scores and the Oswestry Disability Index (ODI) between the observation group and the control group before the treatment were not statistically significant (P>0.05 in both). However, four weeks and eight weeks after the treatment, the VAS scores and the ODIs were significantly lower in both groups than those before the treatment (P<0.05 in both). In terms of the therapeutic efficacy, eight weeks after the treatment, the total effective rates in the control group and the observation group were 67.7% and 87.5%, respectively, with the observation group being superior to the control group (P<0.05). Conclusion. After RFAT, interventional circulatory perfusion combined with autologous PRP intramedullary injection in the lumbar disc is a safe and effective treatment for DLBP, and it had superior long-term effects in improving the clinical symptoms and patient dysfunction than the RFAT and interventional circulatory perfusion.